The Role Of Ethics In Business Activities: Study Of Values And Morals In Islamic Business - Mashuri Mashuri; Irawan Fakhrudin Mahalizikri (Institut Nalanda, 2023)
This study aims to determine how the role of ethics in business activities for business people. The analysis performed in this research is descriptive analysis. The data used is in the form of library data. Based on the author's analysis in this study it was found that business ethics plays a very large role in business activities. This can be illustrated in the Prophet Muhammad in business practices. He is very siddiq, trustworthy, fathanah. The result of applying these principles brought success to him. Thus it can be said that anyone who adopts these ethical principles will be successful in running a business. There is a decline in doing business among today's business people because they only follow their passions and ignorance of the advantages of these principles. So it is not surprising that the business carried out is synonymous with dirty deeds, such as lying, betrayal, broken promises, deceit and so on. Either because they are forced by economic needs, they do it alone or conspire with other people illegally or because of intense competition that makes them do things that are forbidden in religion. If this is what applies to a businessman, then it will be a loss that he will gain both in this world and in the hereafter.